Efforts To Improve Learning Results In 100 Meter Short Distance Running Through The Play Approach In Class VII Students of SMP Negeri 29 Rumbia, Bombana District - Hardiman Amiruddin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2023)
This study aims to determine the increase in learning outcomes of 100 meter short distance running through a playing approach in class VII students of SMP Negeri 29 Rumbia. This research was conducted in class VII of SMP Negeri 29 Rumbia in the odd semester of the 2021/2022 Academic Year. The subjects studied were students of class VII, totaling 16 students, with details of 13 male students and 3 female students. The factors observed in this study are student factors. This research was carried out in 2 (two) cycles, including: (a) planning; (b) implementation of actions; (c) observation; and (d) reflection. The data obtained in this study were analyzed using descriptive statistics. The results showed that the application of the playing method could improve the learning outcomes of short-distance running in class VII students of SMP Negeri 29 Rumbia, with an average achievement in cycle 1 of 64.58, an average of 71.87 in cycle 2, and an average of cycle 3 average obtained 80.2.